Urgensi Komunikasi Interpersonal Kepala Keluarga Dalam Membangun Keluarga Sakinah - Muhammad Randicha Hamandia; Firnadia Firnadia (Journal of Communication Studies, 2022)
The interpersonal communication skills of the head of the family in building a sakinah family are very important to note because remembering that the pattern of communication that exists within a family will determine the success of building a peaceful household. Good communication will make it easier to achieve household goals that have been planned beforehand. This research is a type of field research with a qualitative descriptive method. The analysis technique uses content analysis. Data collection tools are observation, interviews, and documentation. The theory used in this research is interpersonal communication theory. The author uses this theory because the theory of interpersonal communication will provide mutual openness between the head of the family to family members so that effective communication will be easily achieved. The results of this study show that the ability of the head of the family to establish interpersonal communication with other family members in creating a sakinah family as a whole has achieved effective and open communication. Furthermore, the head of the family is able to build a sakinah family, this can be seen from the relatively long age of marriage and the lack of internal conflict that occurs. Keywords: Sakinah Family, Interpersonal Communication Skills